Direct Percutaneous Endoscopic Jejunostomy: Procedural and Nutrition Outcomes in a Large Patient Cohort. Issue 5 (27th December 2017) - Simoes, Priya K.; Woo, Kaitlin M.; Shike, Moshe; Mendelsohn, Robin B.; Gerdes, Hans; Markowitz, Arnold J.; Ludwig, Emmy; Shah, Pari M.; Schattner, Mark A.
Abstract: Background: Direct percutaneous endoscopic jejunostomy (DPEJ) is used for enteral nutrition (EN) in patients with postoperative anastomotic leaks after esophagectomy/gastrectomy and at high risk for aspiration. We characterized the indications, technical success, procedural/nutrition outcomes, and adverse events in a large cohort of patients undergoing DPEJ insertion. Methods: Patients undergoing DPEJ insertion between January 2009 and March 2015 were identified from an institutional endoscopy database. Demographic, procedural, and nutrition outcome data were collected from electronic medical records. Regression analyses were used to identify predictors of adverse events and procedural success. Results: A total of 452 patients underwent 480 attempts at DPEJ insertion. Indications included preoperative or postoperative weight loss (64%), postoperative upper gastrointestinal (UGI) anastomotic leak (13%), aspiration prevention (10%), and other (13%). Of attempted procedures, 398 (83%) were successful. Feeding was initiated in 389 (98%) of patients; a median of 1775 calories was delivered daily. Median body mass index (BMI) at baseline was 22.9 (11.4–44.7) and did not change over follow‐up. Median change in BMI after DPEJ was similar in groups that received EN with palliative and curative intent. Adverse events following 480 attempted DPEJ insertions included 13 (3%) immediate and 74 (15%) delayed, 13 (3%) of which were serious. Patients with head and neck cancer had more adverse events than those with esophageal cancer ( P = .020). Conclusion: DPEJ is a successful and safe procedure that effectively provides access for EN support in malnourished patients and patients with postoperative UGI cancer.